(untitled) - McCuen, Jo Ray (San Diego, 1987)
Rewriting Writing: A Rhetoric comes in two versions, hardback and paperback. The hardback version contains a handbook that covers familiar matters of grammar, syntax, and mechanics; the paperback is identical to the hardback, except that it has no handbook.
Keywords: Report writing,Tiếng Anh,Phương pháp viết báo cáo,English language; Tu từ học,Rhetoric